The Effects of Physiological Demands on Visual Search Behaviours During 2 vs. 1 + GK Game Situations in Football: An in-situ Approach - Casanova, Filipe; Esteves, Pedro T.; Padilha, Maickel Bach; Ribeiro, João; Williams, Andrew Mark; Garganta, Júlio (Frontiers in Psychology, 2022)
We examined the effect of physical workload on gaze behavior during defensive performance in 2vs1+Gk game situations. Twenty-two football players were allocated to two groups (high- and low-performing) based on their defensive tactical performance. A total of 12 game sequences (trials) were presented under high- and low-workload conditions. At the end of each sequence, participants were asked to indicate their perceived exertion using the Rating Scale of Mental Effort and the Borg Scale. The low- and high-workload conditions were defined when the players achieved 60% and 90% of their HRmax, respectively, as per their performance in the Yo-Yo Intermittent Recovery Test. Visual search behaviors were recorded using Tobii Pro eye-movement registration glasses. Players reported an increase in RPE values from the low- to high-workload conditions. The low-performing group increased fixation duration and decreased the number of fixations and number of fixation locations from the low- to high-workload conditions. Both groups displayed different visual search strategies with regards the areas of interest fixated upon. Participants in the high-performing group tended to focus on the SpaceFrontPlayer, followed by Ball and AnotherOpponent. The low-performing group spent more time focusing on the SpaceFrontPlayer and SpacePlayer than Ball and AnotherOpponent. Our results suggest that physical workload and game expertise may hold a differential effect on the visual search behaviors of football players. Coaches and practitioners may resort to the manipulation of individual and task constraints while attending to the close interplay between physical workload, visual behavior and tactical performance during football practice.